2019
DOI: 10.1002/bem.22239
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Assisted Enzyme‐Catalyzed Hydrolysis of Collagen to Produce Peptides With Biomedical Potential: Collagenase From Aspergillus terreus UCP1276

Abstract: Ultrasound has been applied for varied purposes as it provides additional mechanical energy to a system, and is still profitable and straightforward, which are advantages for industrial applications. In this work, ultrasonic treatments were applied to purified collagenase fractions from a fermented extract by Aspergillus terreus UCP 1276 aiming to evaluate the potential effect on collagen hydrolysis. The physical agent was evaluated as an inductor of collagen degradation and consequently as a producer of pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Besides, it has been reported that the enzyme activity can be enhanced by ultrasonic treatment under optimized conditions utilizing its thermal effect, mechanical fluctuant effect and cavitary effect [ 16 ]. UCE can not only improve the extraction efficiency but also enhance the quantity of the extracts [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. As we know, there are few studies about extracting flavonoids and polyphenols from the Nymphaea hybrid , especially few reports on how to extract flavonoids sufficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it has been reported that the enzyme activity can be enhanced by ultrasonic treatment under optimized conditions utilizing its thermal effect, mechanical fluctuant effect and cavitary effect [ 16 ]. UCE can not only improve the extraction efficiency but also enhance the quantity of the extracts [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. As we know, there are few studies about extracting flavonoids and polyphenols from the Nymphaea hybrid , especially few reports on how to extract flavonoids sufficiently.…”
Section: Introductionmentioning
confidence: 99%